Selective Glycopolymer Inhibitors of Galectin-3: Supportive Anti-Cancer Agents Protecting Monocytes and Preserving Interferon-Gamma Function - Filipová, Marcela; Tavares, Marina Rodrigues; Hovorková, Michaela; Heine, Viktoria; Nekvasilová, Pavlína; Křen, Vladimír; Etrych, Tomáš; Chytil, Petr; Bojarová, Pavla (International journal of nanomedicine, 2025)
INTRODUCTION: The immunosuppressive roles of galectin-3 (Gal-3) in carcinogenesis make this lectin an attractive target for pharmacological inhibition in immunotherapy. Although current clinical immunotherapies appear promising in the treatment of solid tumors, their efficacy is significantly weakened by the hostile immunosuppressive tumor microenvironment (TME). Gal-3, a prominent TME modulator, efficiently subverts the elimination of cancer, either directly by inducing apoptosis of immune cells or indirectly by binding essential effector molecules, such as interferon-gamma (IFNγ). METHODS: N-(2-Hydroxypropyl)methacrylamide (HPMA)-based glycopolymers bearing poly-N-acetyllactosamine-derived tetrasaccharide ligands of Gal-3 were designed, synthesized, and characterized using high-performance liquid chromatography, dynamic light scattering, UV-Vis spectrophotometry, gel permeation chromatography, nuclear magnetic resonance, high-resolution mass spectrometry and CCK-8 assay for evaluation of glycopolymer non-toxicity. Pro-immunogenic effects of purified glycopolymers were tested by apoptotic assay using flow cytometry, competitive ELISA, and in vitro cell-free INFγ-based assay. RESULTS: All tested glycopolymers completely inhibited Gal-3-induced apoptosis of monocytes/macrophages, of which the M1 subtype is responsible for eliminating cancer cells during immunotherapy. Moreover, the glycopolymers suppressed Gal-3-induced capture of glycosylated IFNγ by competitive inhibition to Gal-3 carbohydrate recognition domain (CRD), which enables further inherent biological activities of this effector, such as differentiation of monocytes into M1 macrophages and repolarization of M2-macrophages to the M1 state. CONCLUSION: The prepared glycopolymers are promising inhibitors of Gal-3 and may serve as important supportive anti-cancer nanosystems enabling the infiltration of proinflammatory macrophages and the reprogramming of unwanted M2 macrophages into the M1 subtype.
Keywords: galektin 3; nádorové mikroprostředí; interferon-gamma; Interferon-gamma; protinádorové látky; monocyte; Blood Proteins; monocyty; galectin-3; Acrylamides; interferon gama; Galectin 3; carbohydrate; glycopolymer; Galectins; Polymers; krevní proteiny; lidé; polymery; Humans; Monocytes; makrofágy; akrylamidy; apoptóza; tumor microenvironment; Macrophages; galektiny; Tumor Microenvironment; Apoptosis; Antineoplastic Agents